International child abduction, domestic violence and the future of the Hague convention of 1980 : a preliminary analysis of the colombian constitutional court's review of the losice case (2018)
"Hundreds of women victims of domestic violence are obliged to leave their countries of residence in company of their children. However, under the application of The Hague Convention of 1980 women are later required to return their children to the father. Currently, Colombia's Constitutional Court is reviewing a case reflecting this same pattern. This article focuses on the question of whether domestic violence is included as an exception to the international restitution of children contemplated in article 13 of The Hague Convention. To answer this question, the text analyzes the relation between human rights and private international law, the impact of gender perspective and the supremacy of children's rights." -- Tomado del Formato de Documento de Grado.